2011
DOI: 10.4049/jimmunol.1002928
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-Derived Suppressor Cells Infiltrate the Heart in Acute Trypanosomacruzi Infection

Abstract: Chagas disease, caused by the protozoan parasite Trypanosoma cruzi, affects several million people in Latin America. Myocarditis, observed in the acute and chronic phases of the disease, is characterized by a mononuclear cell inflammatory infiltrate. We previously identified a myeloid cell population in the inflammatory heart infiltrate of infected mice that expressed arginase I. In this study, we purified CD11b+ myeloid cells from the heart and analyzed their phenotype and function. Those CD11b+ cells were ∼7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
82
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(94 citation statements)
references
References 32 publications
11
82
0
Order By: Relevance
“…After blood removal by perfusion, parasite DNA was purified from cardiac tissue with the High Pure PCR Template preparation Kit (Roche), and PCR reactions were performed with 100ng of DNA as described Cuervo et al, 2011).…”
Section: Parasite Dna Detection and Mrna Analysis By Quantitative Rt-mentioning
confidence: 99%
“…After blood removal by perfusion, parasite DNA was purified from cardiac tissue with the High Pure PCR Template preparation Kit (Roche), and PCR reactions were performed with 100ng of DNA as described Cuervo et al, 2011).…”
Section: Parasite Dna Detection and Mrna Analysis By Quantitative Rt-mentioning
confidence: 99%
“…For example, the inflammatory heart infiltrate from mice infected with Trypanosoma cruzi consisted mainly of CD11b + Ly6G -Ly6C + MDSCs [85]. These cells exhibited a monocytic phenotype and expressed arginase-1 and iNOS, both of which can suppress T-cell proliferation and prevented clearance of the parasite.…”
Section: Mdscs In Other Pathological Conditionsmentioning
confidence: 99%
“…More recently, these authors reported the predominant induction of M-MDSCs in cardiac lesions of BALB/c mice infected with T. cruzi Y strain. These cells expressing iNOS/arginase-1 use suppressive mechanisms such as NO production and depletion of arginine by arginase-1 [10].In a previous study analyzing the innate immunity induced in BALB/c and C57BL/6 (B6) mice after Tulahuen strain T. cruzi infection [21], we observed that B6 showed higher morbidity and mortality compared with BALB/c mice which demonstrated better tissue repair. In addition, increased and persistent levels of TNF-α, IL-6, IL-12, and IL-1β proinflammatory cytokines and very low IL-10 and TGF-β were present in the liver of B6 mice.…”
mentioning
confidence: 91%
“…This shift in iNOS activity most likely reflects the crosstalk of iNOS with other enzymes such as NADPH oxidase to promote the production of peroxynitrites, which inhibits the proliferation and effector function of T cells [2]. MDSCs use several mechanisms in addition to the production of ROS and NO, such as triggering apoptosis of activated T cells by depleting of L-arginine, via arginase [7][8][9][10]. There is also evidence that MDSCs may suppress immune activation by inducing T regulatory cell expansion [11].…”
mentioning
confidence: 99%